(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The objective of this work was to formulate and analyze microsponges of nicotinamide. The said formulation was created using the emulsion solvent diffusion technique, and a 3 level two factor-based factorial design was applied to optimize the effect of the stabilizer (X1), as well as drug (X2), amounts on the entrapment efficiency (Y1) and average particle size (Y2). Various parameters, such as flow characteristics, percentage yield, drug concentration, in-vitro drug release tests, entrapment efficiency, and scanning electron microscopy (SEM), were evaluated. All parameters were found to be within the acceptable range. Design Expert 13 was employed to optimize the microsponges, and the optimal batch was determined by examining the desirability data. From this analysis, the optimal amounts of drug and stabilizer were found to be 302.87 and 59.71 mg, respectively. The reliability of the preparation and evaluation of the optimized batch was confirmed by a less than 5% discrepancy between the observed and predicted values of parameters. SEM images revealed that the microsponges were prepared with uniform and spherical morphology. The study concluded that nicotinamide microsponges were successfully prepared and evaluated. Further steps will involve incorporating this formulation into a novel topical dosage form.